The Influence of Glycosylation on the Catalytic and Fibrinolytic Properties of Pro-Urokinase - Lenich, Catherine; Pannell, Ralph; Henkin, Jack; Gurewich, Victor (Thrombosis and Haemostasis, 1992)
We previously found that human pro-UK expressed in Escherichia coli is more active in fibrinolysis than recombinant human pro-UK obtained from mammalian cell culture media. To determine whether this difference is related to the lack of glycosylation of the E. coli product, we compared the activity of E. coli-derived pro-UK [(-)pro-UK] with that of a glycosylated pro-UK [(+)pro-UK] and of a mutant of pro-UK missing the glycosylation site at Asn-302 [(-) (302) pro-UK]. The latter two pro-UKs were obtained by expression of the human gene in a mammalian cell. The nonglycosylated pro-UKs were activated by plasmin more efficiently (≈2-fold) and were more active in clot lysis (1.5-fold) than the (+)pro-UK. Similarly, the nonglycosylated two-chain derivatives (UKs) were more active against plasminogen and were more rapidly inactivated by plasma inhibitors than the (+)UK.These findings indicate that glycosylation at Asn-302 influences the activity of pro-UK/UK and could be the major factor responsible for the enhanced activity of E. coli-derived pro-UK.